IDD and mesoscale model integrated system IDD y el sistema integrado del modelo de mesoescala - Lia Martins Costa do Amaral; C. T. Homann; Y. Yamasaki (Meteorologica, 2011)
As part of the group of research institutions and universities participating in the UNIDATA program, the Federal University of Pelotas (RS-Brazil) has implemented an automatic data acquisition with forecasting and synoptic analysis system. It is based on the data distribution system (IDD) of the UNIDATA (University Data Project) and uses the Local Data Management module (LDM). This is an integrated system which has been primarily implemented to use the GFS/NCEP global forecasting model data for the processing of the regional MM5 mesoscale model, providing the necessary initial and lateral boundary conditions data. The MM5 has been configured to provide the forecast of the mesoscale systems over the State of Rio Grande do Sul (RS). The use of the data and model integrated system contributes to improve the skill analysis of the model output, aiming to investigate the benefits of its association in the evaluation of the performance of the integrated system.